Development of carbone fiber-reinforced polypropylene composite for car bumpers - Zahari, Nor Hasni (2009)
Carbon fiber reinforced composites (CFRC) are very strong and extremely lighter than steel. Their toughness provides excellent abrasion and tear resistance. The usage of the CFRC in automotive industries is widely explored due to the new requirements related to energy conservation, safety and antipollution. In this study, discontinuous carbon fiber reinforced polypropylene composite was selected due its characteristics such as light-weight, corrosion resistance, low to moderate cost, thermal stability and ease of fabrication. Polypropylene (PP) was chosen as the matrix because it is available in large quantities and not very sensitive to chemical stress cracking. PP also has a combination of high elongation and tensile strength. Carbon fibers are widely used in polymer–matrix composites owing to their good mechanical, thermal and electrical properties. Cheap discontinuous carbon fiber or short fiber is the low quality carbon fiber which cannot be used in aircraft and aerospace industry which requires high quality continuous-fiber laminates as primary structures. The composite was developed to fill the mechanical property gap between the discontinuous-fiber composites and the un-reinforced polymers used in non-load-bearing applications. The objectives of this work are to develop carbon fiber polypropylene composite under various process conditions, and to investigate the mechanical and thermal properties of carbon fiber polypropylene composite. In this study, two different types of polypropylene composites were produced by mixing and compressing the mixtures using hot press. In the first stage, the mixture was prepared by mixing polypropylene with chopped carbon fiber and carbon fiber percentage (wt%) was varied. The composites were evaluated for mechanical properties. Mixing time,mixing temperature and rotor speed were varied to determine the best conditions. Among the mechanical testing and analysis investigated were tensile test, impact test,bending test and density test. Whilst the, the Scanning Electron Microscopy (SEM) was employed to study the morphology of the composites and Dynamic mechanical analysis (DMA) and Thermal gravimetric analysis (TGA) were used to determine the thermal properties. The highest tensile strength was obtained for polypropylene with melt flow index 60 (MFI 60) composites reinforced with 10 wt% carbon fiber. The composite also showed the best tensile and flexural properties. TGA analysis of composite with 10 wt% carbon fiber content revealed excellent thermal stability compared to the plain polypropylene. The performance of the selected composite was comparable to a local commercial car bumper.